Studi Pengaruh Pengaturan Sistem Pergerakan Kendaraan Terhadap Kinerja Ruas Jalan Yos Sudarso Di Kota Tarakan - Zultan M, Achmad; Setiawan, Budi (Jurusan Teknik Sipil, 2018)
Jl. Yos Sudarso is one of the centers of movement in Tarakan or a business zone. Jl. Yos Sudarso has experienced an increase in road load and a decrease in the level of road services which will eventually cause traffic problems, namely the effectiveness of reduced traffic performance. To find out the analysis of traffic performance due to the arrangement of the vehicle movement system on Yos Sudarso Tarakan road, traffic surveys are carried out, such as traffic volume, traffic speed, road capacity, and degree of saturation. After the road performance analysis, the characteristics and conditions of the road were obtained, the average total volume was 1399.92 pcu / hour, the average degree of saturation on the Yos Sudarso road in the direction of Kusuma Bangsa was 0.53, while the direction of Mulawarman was 0,55. Thus the average performance along Yos Sudarso road includes the C service level. By looking at these conditions it is necessary to increase the clear traffic flow regulation system such as traffic signal so that it can reduce the congestion that occurs on these roads. The construction of the coastal road frontage line and the construction of the access road network will provide benefits in the form of a road network in the western part of Tarakan city, reducing traffic density points.